Cross-cultural adaptation of the primary health care satisfaction questionnaire - Paz,Elisabete Pimenta Araujo (2014)
Objective To develop the cross-cultural validation and assessment of the psychometric properties of the Questionnaire about the quality and satisfaction dimensions of patients with primary health care. Methods Methodological cultural adaptation and assessment study of the psychometric properties, involving 398 users from a primary care service. The construct validity was verified through principal components factor analysis and internal consistency assessment as determined by Cronbach’s alpha, using SPSS. Results A factorial structure was identified that is equivalent to the original instrument, showing six factors that explain 70.81% of the total variance. All internal consistency coefficients were higher than 0.84, indicating appropriate psychometric properties. Conclusion The results show that the Brazilian Portuguese version of the instrument is culturally and linguistically appropriate to assess the satisfaction of users attended in primary care services.